2019
DOI: 10.1177/0018578719844168
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of Y-Site Injection of Meropenem Trihydrate With 101 Other Injectable Drugs

Abstract: Objective: The objective of the study was to establish the compatibility of injectable meropenem with 101 other drugs during Y-site administration. Methods: Meropenem (50 mg/mL, 10 mL) was combined with 101 undiluted injectable drugs (10 mL each) at room temperature. Each preparation was performed twice. The first sample underwent a visual evaluation and a particle count test by light obstruction immediately after mixing. These tests were repeated 4 hours after mixing using the second preparation. Incompatibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Studies reported that pH changes of intravenous drug solution within the range of 0.2 to 1.0, the solution was stable and compatible [19][20][21][22]. Dotson et al defined physical incompatibility as a pH value of no more than 10% change from baseline (0 hour) after 48 hours [15].…”
Section: Plos Onementioning
confidence: 99%
“…Studies reported that pH changes of intravenous drug solution within the range of 0.2 to 1.0, the solution was stable and compatible [19][20][21][22]. Dotson et al defined physical incompatibility as a pH value of no more than 10% change from baseline (0 hour) after 48 hours [15].…”
Section: Plos Onementioning
confidence: 99%
“…Ten percent of the gaps in our review are related to meropenem, much more than the rest of other antimicrobials studied. Latest published data show incompatibility with key drugs, such as dobutamine and vancomycin 45,46 …”
Section: Resultsmentioning
confidence: 99%
“…Latest published data show incompatibility with key drugs, such as dobutamine and vancomycin. 45,46 In addition, the compatibility of ceftolozane-tazobactam with different i.v. drugs during Y-site administration was also analysed.…”
Section: Beta-lactam Antibioticsmentioning
confidence: 99%